The anthropology of climate change : an integrated critical perspective - Baer, Hans A., 1944-; Singer, Merrill (Routledge advances in climate change research., 2018)
"In addressing the urgent questions raised by climate change, this book provides a comprehensive overview of the anthropology of climate change, guided by a critical political ecological framework. It examines the emergence and slow maturation of the anthropology of climate change, reviews the historic foundations for this work in the archaeology of climate change, and presents three alternative contemporary theoretical perspectives in the anthropology of climate change. This second edition is fully updated to include the most recent literature published since the first edition in 2014. It also examines a number of new topics, including an analysis of the 2014 American Anthropological Association's Global Climate Change Task Force report, a new case study on responses to climate change in developed societies, and reference to the stance of the Trump administration on climate change. Not only does this book provide a valuable overview of the field and the key literature, but it also gives researchers and students in Environmental Anthropology, Climate Change, Human Geography, Sociology, and Political Science a novel framework for understanding climate change that emphasizes human socioecological interactions."--Provided by publisher.